2020
DOI: 10.1021/acs.oprd.0c00482
|View full text |Cite
|
Sign up to set email alerts
|

Development and Scale-Up of an Improved Manufacturing Route to the ATR Inhibitor Ceralasertib

Abstract: Ceralasertib is currently being evaluated in multiple phase I/II clinical trials for the treatment of cancer. Its structure, comprising a pyrimidine core decorated with a chiral morpholine, a cyclopropyl sulfoximine and an azaindole, makes it a challenging molecule to synthesize on a large scale. Several features of the medicinal chemistry and early development route make it unsuitable for the long-term commercial manufacture of the active pharmaceutical ingredient. We describe the investigation and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Thus, a new literature project was invented for the remote students. The students were each given a journal article from Organic Process Research and Development that described the development of a process to synthesize a drug on a large scale. Process research is highly concerned with the specifics of the experimental procedures. A good process must be able to be carried out on a large scale, with high reproducibility, high yield, high purity, safe conditions, minimization of environmental hazards and waste, and low cost .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a new literature project was invented for the remote students. The students were each given a journal article from Organic Process Research and Development that described the development of a process to synthesize a drug on a large scale. Process research is highly concerned with the specifics of the experimental procedures. A good process must be able to be carried out on a large scale, with high reproducibility, high yield, high purity, safe conditions, minimization of environmental hazards and waste, and low cost .…”
Section: Discussionmentioning
confidence: 99%
“…This stereospecific NH transfer to sulfoxides, has been adopted into the manufacturing scale production of ATR Inhibitor AZD6738 (Ceralasertib) from AstraZeneca. [33][34][35][36][37] Graham et al reported the preparation of the sulfoximine containing intermediate 6 from the corresponding sulfoxide 5 (Scheme 8).…”
Section: Synthesis Of Nh-sulfoximinesmentioning
confidence: 99%
“…44 However, drawbacks such as the need for the hydrolysis of the acetamide and the cost of rhodium acetate prompted Graham and coworkers to propose an alternative strategy based on the imination of sulfoxide developed by Bull and Luisi but with few modifications (Scheme 16, b). 45 In particular, the reaction was performed at 5 °C and by decreasing the equivalents of PIDA (2.1 instead of 3 equivalents) to control the impurities formation. Moreover, a mixture of methanol and toluene was adopted as a suitable reaction solvent for this transformation.…”
Section: One-pot Nh and O Transfer For The Synthesis Of Biologically Active Compoundsmentioning
confidence: 99%